(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Biopharmaceuticals have emerged as a cornerstone of modern medicine, offering targeted and effective treatments for a diverse array of medical conditions. This review provides an overview of the key applications, challenges, and opportunities in biopharmaceutical development. Key applications include cancer immunotherapy, rare genetic disorders, autoimmune diseases, infectious diseases, and neurological disorders. Challenges such as complex manufacturing processes, regulatory requirements, and high costs are discussed, alongside opportunities arising from advances in biotechnology, personalized medicine, and collaborative partnerships. The importance of prioritizing patient safety, accessibility, and affordability is emphasized. By embracing innovation and collaboration, the biopharmaceutical industry can continue to revolutionize healthcare and improve patient outcomes.